Morphology and electrophoretic protein profiles of female salivary glands in four Oriental black fly species (Diptera: Simuliidae) - Jariyapan N. (2014)
Saliva of female flies is responsible for localized hypersensitivity reactions and life-threatening systemic hemorrhagic syndromes in humans and animals. In this study, morphology and electrophoretic protein profiles of female salivary glands of Oriental black flies in the subgenus Simulium Latreille s. str., Simulium (Simulium) nigrogilvum, S. (S.) rufibasis, S. (S.) nodosum, and subgenus Gomphostilbia Enderlein, S. (Gomphostilbia) asakoae were analyzed. The paired female salivary glands of the four simuliid species were morphologically similar and situated on either side of the esophagus. Each gland is composed of two main parts, a secretory arm and a reservoir. In each species, the size of the gland correlated with salivary gland protein contents. SDS-PAGE analysis revealed differences of electrophoretic protein profiles and specifically major protein bands of the female salivary glands in each species, suggesting that protein profiles might be useful for construction of an additional tool to distinguish these black fly species. The information obtained from this study is an initial step for further research on salivary proteins that are involved in vertebrate hemostatic response.